The Cypriot food basket for health and adequate social participation - Chrysostomou, Stavri; Polycarpou, Alexandros; Andreou, Sofia N.; Pashardes, Panos (My University, 2016)
Introduction: Besides its nutritional function, food also serves a range of other human needs that are important to ensure an adequate participation in the society. Aim: To assess the cost of the Cypriot food basket (FB) fulfilling physical and non-physical needs as a part of the pilot project for the development of a common methodology for comparable reference budgets in all EU countries. Materials and methods: 24 adult subjects were randomly assigned into 3 focus groups (FGs). HFBs were developed for 6 different types of households living in the capital city and were based on the Cypriot National Guidelines for Food and Exercise. FGs have discussed the HFB, the other food functions (non-physical needs) and the buying habits. Afterwards, adaptations in the food baskets and the pricing were conducted.
Keywords: Cost; Cypriot food basket